Prevalence of oral mucosal lesions among the institutionalized elderly people - Petrovski Mihajlo (Acta Stomatologica Naissi, 2024)
Background: The presence of mucosal changes and variations is quite high among institutionalized adults. Aim: The present study aimed to determine the prevalence of oral mucosal changes among the institutionalized elderly. Material and method: The presented data originate from research done in the period from May-July 2018 in "Mother Teresa" nursing home in Skopje, Republic of North Macedonia. The investigation included a total number of 70 subjects older than 65 years and it was focused on the presence of mucosal changes. In describing the changes in oral mucosa we have used two differentiated termslesion or pathological change and variation from normal. Results: During the examination of the prevalence of oral mucosal lesions we have found that all the subjects have at least one oral change in their oral cavity. The average number of oral changes among the examined institutionalized elderly is 2,24 ± 0,69. Total number of diagnosed changes on oral mucosa among all 70 subjects was 157. In the group of normal mucosa, variations dominate status fordyce (35.71 %) and coated tongue (28,57%). In the group of pathological changes, there is a domination of the lesions associated with the wearing of prosthetic devices-ulcerous changes caused by the prosthetic devices (15.71%) and stomatitis protetica (10%). Conclusion: In the investigated population, there is a one hundred percent presence of oral changes. Most of them are variations of the oral mucosa. But more important pathological lesions are those associated with wearing prosthetic devices. Also, it is very important to stress that pathological lesions require constant monitoring.